Gestational Age Variation in Human Placental Drug Transporters - Goetzl, Laura; Darbinian, Nune; Merabova, Nana; Devane, Lindsay C.; Ramamoorthy, Sammanda (Frontiers in Pharmacology, 2022)
Patient and providers fear of fetal exposure to medications may lead to discontinuation of treatment, relapse, and maternal morbidity. Placental drug transporters play a critical role in fetal exposure through active transport but the majority of data are limited to the third trimester, the least critical time period in development. Our objective was to define gestational age dependent changes in protein activity, expression and modifications of five major placental drug transporters: SERT, P-gp, NET, BCRP and MRP-3. Apical brush border membrane fractions were prepared from fresh 1st, 2nd and 3d trimester human placentas collected following elective pregnancy termination or planned cesarean delivery. A structured maternal questionnaire was used to identify maternal drug use and exclude all exposed subjects. Changes in placental transporters activity and expression relative to housekeeping proteins by quantitative western blotting. There was evidence for strong developmental regulation of SERT, NET, P-gp, BRCP and MRP-3. P-gp and BRCP decreased with gestation (r=-0.72, p<0.001 and r=-0.77, p<0.001, respectively). Total SERT increased with gestation but this increase was due to a decrease in SERT cleavage products across trimesters. Uncleaved SERT increases with GA (r= 0.89, p<0.001) while cleaved SERT decreases with GA (r=-0.94, p<0.001). Apical membrane NET may increase slightly in the second trimester, but overall did not appear to be developmentally regulated (r=-0.08, p=0.53). Two forms of MRP-3 were identified; the 50 kD form did not change across GA; the 160kD form was steady in the first and second trimester and increased in the third trimester (r=0.24, p=0.02). The 50kD form was expressed at higher levels. The observed patterns of SERT, NET P-gp, BRCP and MRP-3 expression and activity may be associated with transporter activity or decrease placental permeability in the first trimester to transporter specific substrates including commonly used medications such as anti-depressants, anti-psychotics, amphetamines, protease inhibitors, and some antibiotics, while transport of nutrients and serotonin is important in the first trimester. Overall these observations are consistent with a strong protective effect during organogenesis. Third trimester estimates of fetal exposure obtained from cord blood likely significantly overestimate early fetal exposure at any fixed maternal dose.